ASSOCIATION AMONG STATIN, TELOMERE LENGTH AND CARDIOVASCULAR DISEASES - Bijukchhe, Sanjeev; Isnuwardana, Ronny; Rattanasiri, Sasivimol; Thadanipon, Kunlawat; Thakkinstian, Ammarin (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2019)
Background: Recent evidence has shown associations between cardiovascular diseases (CVDs) and telomere length (TL). Many factors affect telomerase activity (TA) and TL, and statin was recently found to be associated with TA and TL. This systematic review and meta-analysis was conducted to summarize the evidence on the effect of statin on TA and TL, and update the knowledge of association between TL and CVDs. Primary objective is to determine the effect of statin on TA and TL; Secondary objective, to assess the associations between TL and CVDs.Methods: The MEDLINE and Scopus databases were searched to identify eligible studies and extracted data. Meta-analysis was done to see effects of statin on TA/TL [i.e., standardized/unstandardized mean difference (SMD/USMD)] and TL on CVDs using random-effects and fixed-effects model according to heterogeneity assessed by Q test and I2.Results: Five and 18 studies were selected for the primary and secondary objectives, respectively. Pooled TA showed effect of statin on TA with SMD [95% confidence interval (CI)] of 1.90 (1.16, 2.64) TA. However, no significant effect on TL was seen. Increased risk of CHD among participants with shorter TL was estimated by a pooled risk ratio of 1.58 (1.19, 2.09). However, pooled hazard ratios (HRs) for CHD and stroke were non-significant; but shorter TL was significantly increased risk for unspecified CVDs with pooled HR of 1.33 (1.04, 1.70).Conclusions: Our study showed association between statin and TA, but not for TL. In addition, shorter TL is more likely to be higher risk for CHD and unspecified CVDs. However, results were still inconclusive based on different pooled parameters. More studies are required to confirm the association of statin with TL, possibly to elucidate its protective effect on CVDs.